Sensitivity analysis of airfoil aerodynamics during pitching motion at a Reynolds number of 1.35×105. Issue 183 (December 2018) - Geng, F.; Kalkman, I.; Suiker, A.S.J.; Blocken, B.
Abstract: Numerically reproducing wind tunnel experimental tests of flow behavior around a pitching airfoil is a challenge, especially under the occurrence of dynamic stall at relatively high angles of attack. This not only requires the application of advanced turbulence models, but also asks for examining the influence of the most relevant model parameters in detail. This contribution presents the results of an extensive computational study of the unsteady flow around a pitching NACA0012 airfoil at a Reynolds number of 1.35 × 10 5, as obtained by first performing 2D Unsteady Reynolds-Averaged Navier-Stokes (URANS) simulations whereby the flow characteristics are simulated by the Transition SST turbulence model. The influence of a large number of parameters on the numerical results is investigated, namely the blockage ratio, computational grid resolution and y + value, time step size, inlet freestream turbulence properties, airfoil trailing edge detailing and turbulence model. Integral aerodynamic force coefficients and detailed flow patterns are analyzed and compared with measurements from wind tunnel experiments presented in the literature. For the best-performing parameters, an adequate agreement with the experimental tests is obtained for the upstroke phase, while for the downstroke phase some differences appear. These differences are investigated in more detail by considering the results from a 2.5D Large Eddy Simulation (LES), which provides deep and complementary insights into the flow behavior during dynamic stall at the selected Reynolds number. Highlights: 2.5D LES and URANS simulations show significant flow unsteadiness during the downstroke phase. During the downstroke phase the aerodynamic forces are relatively sensitive to changes in the computational parameters. The location of flow separation, flow transition point and boundary layer height are critically dependent of flow conditions.